A Local Review on the Use of a Bio-Psycho-Social Model in School-Based Mental Health Promotion - Wong, Anna; Chan, Iris; Tsang, Christy H. C.; Chan, Anna Y. F.; Shum, Angie K. Y.; Lai, Eliza S. Y.; Yip, Paul (Frontiers in Psychiatry, 2021)
Background: Schools are a key setting for student well-being promotion. Various school-based mental health programs have been implemented worldwide, with greater emphasis placed on psychological and social aspects. The bio-psycho-social model provides a holistic and integrated view of mental health based on theory and research evidence. Given the importance of considering all three dimensions in mental health promotion, this study explored reasons for the relative neglect of this approach by studying the early phase of school well-being program development and implementation. Method: In total, 77 Hong Kong government-funded student well-being programs implemented in 2000–2009 were reviewed for the use of biological, psychological, and social interventions. Questionnaires and interviews were conducted to explore program leaders' usage and views regarding theoretical frameworks and evidence-based practice and program evaluation. Challenges encountered in the initial stage of school well-being program development and implementation were identified and analyzed. Results: Of the 77 programs reviewed, only 5 addressed all three bio-psycho-social factors of mental health. A significantly greater number of programs addressed psychological (n = 63) and social (n = 40) factors compared to those that covered biological factors of mental health (n = 13). Of 24 program implementers who responded to the online survey, 75% claimed to have studied or applied a theoretical framework yet only 41.7% considered evidence-based practices to be important. The majority of interviewed participants valued their own practical experience over theory and research evidence. Many programs lacked rigorous evaluation of clear objectives and measurable outcomes, thus the mechanisms of change and program effectiveness were uncertain. Perceived barriers to program adoption and continuation were identified. Conclusion: This study highlighted a neglect of the biological contribution to mental health in school well-being promotion initiatives, possibly due to lack of theoretical knowledge and evidence-based practice among program leaders and implementers in the early phase of school mental health promotion. The bio-psycho-social model should therefore be recommended for student well-being programs as a holistic and integrated theory of mental health underpinning program objectives, mechanisms of change, and measurable outcomes. To develop effective practices in student well-being promotion, more thorough documentation, a rigorous evaluation framework, and support for frontline educators to evaluate their practices were recommended.